News Reports: Southern High School, George Soros
A compilation of news reports on George Soros’s financial grant to Southern High School in Baltimore, U.S. It features news from: WB 54 - News at 6:30; Fox 45 - News at Ten; WMAR-TV Baltimore - 2 News.